PENGARUH INTEGRASI PEMASOK, INTEGRASI INTERNAL, INTEGRASI PELANGGAN TERHADAP KINERJA RANTAI PASOKAN YANG DIMODERASI OLEH KETIDAKPASTIAN PERMINTAAN PADA PT X - Adhitya Trubus Hanggara; Kelvin Anthony; Stephanie Stephanie; Sambudi Hamali (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The purpose of this study is to determine the impact of the supplier, internal, and customer integration on supply chain performance moderated by the demand uncertainty at PT X. This study uses quantitative research methods with data collection techniques using questionnaires with a sample number of 38 using saturated sampling techniques. Data analysis with SEM-PLS with WarpPLS 6.0 software. The result of this research is supplier integration, which has a direct impact on supply chain performance, and the integration of suppliers and customers that impact supply chain performance, as moderated by uncertainty in demand. The results of this study show that managers need to improve supplier and customer integration to improve supply chain performance.